The impact of store satisfaction on consumer responses in out-of-stock situations - Grubor, Aleksandar; Milicevic, Nikola; Djokic, Nenad (Review of Business Management, 2017)
Purpose – The purpose of this paper is to test a conceptual model by means of which we try to establish the influence of store satisfaction and other variables (gender, mobility and availability of alternative stores) on consumers’ responses to out-of-stock (OOS) situations. Design/methodology/approach – The authors used a standardized questionnaire to gather data on consumer responses to OOS and then analyzed determinants including store satisfaction (for which reliability, validity and unidimensionality were tested). The survey was conducted in the four largest cities in Serbia. All respondents were interviewed randomly, through telephone calls, whereby 392 responses were gathered. The established hypotheses were tested by means of a multinomial logit model with the use of marginal effects. Findings – The results show that store satisfaction significantly affects three out-of-stock responses (store switching, postponement and product switching), whereas, positively in the case of product switching and postponement and negatively in the case of store switching. The results also show that store satisfied consumers, regardless of other factors, are not likely to switch stores in out-of-stock situations. Originality/value – As well as managerial implications, this paper included store satisfaction as an antecedent of consumer OOS responses for the first time. In addition, the impact of this variable on OOS responses was analyzed at both levels of the availability of alternative stores, gender and mobility.